MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PENYAJIAN DATA MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA SISWA SD - Ma’rifah, Siti; Sunarno, Sunarno (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
“This study aims to improve the mathematics learning outcomes of grade V students of SDN Teluk Dalam 9 Data Presentation material by applying the Problem Based Learning model. The main problems found are the lack of understanding of basic concepts and the lack of active involvement of students in the learning process. This research uses a qualitative approach with the type of Classroom Action Research (PTK) which uses a cycle model design by Kemmis and Taggart which is carried out for two cycles. The type of data used is qualitative data in the form of observations, interviews and quantitative data in the form of student learning outcomes. Data analysis is calculated based on the percentage scale and indicators of classical learning completeness that have been set. The results showed a significant improvement in students' cognitive, affective, and psychomotor learning outcomes. The number of students who were cognitively complete increased from 56.52% of students in the first cycle to 100% of students in the second cycle. In the affective realm, students who showed a positive learning attitude increased from 60.86% to 86.95% of students, while in the psychomotor realm, students' ability to present data increased from 47.82% to 91.30% of students. In addition to increasing learning outcomes, there is also an increase in student and teacher activities in the learning process. Based on the results of this study, it can be concluded that learning using the Problem Based Learning model is effectively used to improve student learning outcomes in mathematics learning, especially in data presentation materials. ABSTRAK Penelitian ini dirancang untuk meningkatkan pembelajaran matematika pada siswa kelas V SDN Teluk Dalam 9, khususnya mengenai materi Penyajian Data melalui penerapan model Problem Based Learning. Masalah utama yang teridentifikasi adalah rendahnya pemahaman terhadap konsep dan minimnya partisipasi aktif para siswa dalam pembelajaran. Dalam penelitian ini, pendekatan yang digunakan adalah kualitatif dengan jenis Penelitian Tindakan Kelas (PTK) yang menerapkan model siklus seperti yang dirancang oleh Kemmis dan Taggart, dilaksanakan dalam dua siklus. Data yang dikumpulkan terdiri dari data kualitatif yang berupa observasi dan wawancara, serta data kuantitatif yang mencakup hasil belajar siswa. Analisis data dilakukan dengan menggunakan skala persentase dan indikator ketuntasan belajar secara klasikal yang telah ditentukan. Hasil yang diperoleh menunjukkan adanya kemajuan signifikan dalam kinerja kognitif, afektif, dan psikomotorik siswa  Jumlah siswa yang mencapai ketuntasan secara kognitif bertambah dari 56,52% pada siklus I menjadi 100% pada siklus II. Dalam aspek afektif, proporsi siswa yang menunjukkan sikap belajar positif meningkat dari 60,86% menjadi 86,95%, sementara dalam aspek psikomotorik, kemampuan siswa dalam penyajian data meluas dari 47,82% menjadi 91,30%. Selain peningkatan hasil belajar, terdapat pula peningkatan dalam aktivitas siswa dan guru selama proses pembelajaran. Berdasarkan temuan ini, dapat disimpulkan bahwa penggunaan model Problem Based Learning terbukti efektif untuk memperbaiki hasil belajar siswa dalam pelajaran matematika, terutama pada materi penyajian data.